Fatigue performance of tubular X-joints: Numerical investigation - Thang, Nguyen Chien; Xudong, Qian; Lan, Ton That Hoang (Vietnam Journal of Mechanics, 2013)
The cyclic actions due to waves, currents and winds on offshore platforms frequently cause fatigue cracks at hot-spot locations. The remaining fatigue life of such connections depends significantly on the fatigue driving force often measured by the stress-intensity factors. This study examines the fatigue performance of tubular joints fabricated using a new type of enhanced partial joint penetration weld details under constant-amplitude brace in-plane bending actions. The numerical study ascertains the crack propagation angle, the crack-front profile and the interaction between adjacent cracks on the stress-intensity factors.